2015
DOI: 10.1002/ange.201502860
|View full text |Cite
|
Sign up to set email alerts
|

Development of Chiral Spiro P‐N‐S Ligands for Iridium‐Catalyzed Asymmetric Hydrogenation of β‐Alkyl‐β‐Ketoesters

Abstract: The chiral tridentate spiro P-N-S ligands (Spiro-SAP) were developed, and their iridium complexes were prepared. Introduction of a1,3-dithiane moiety into the ligand resulted in ah ighly efficient chiral iridium catalyst for asymmetric hydrogenation of b-alkyl-b-ketoesters,p roducing chiral b-alkyl-b-hydroxyesters with excellent enantioselectivities (95-99.9 %e e) and turnover numbers of up to 355 000. AngewandteChemie 8915

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Our group has developed a number of highly effective catalytic asymmetric hydrogenation reactions. [15] [16] We wish to use Ir-catalyzed asymmetric hydrogenation of a β-keto ester [17] to construct a 1,3diol unit and Ir-catalyzed asymmetric hydrogenation of α-acrylic acid, [18] [19] to build the 1,3-methyl unit of deoxypropionates. By varying the configuration of catalysts, the absolute and relative configuration of newly formed stereogenic centers can be controlled.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group has developed a number of highly effective catalytic asymmetric hydrogenation reactions. [15] [16] We wish to use Ir-catalyzed asymmetric hydrogenation of a β-keto ester [17] to construct a 1,3diol unit and Ir-catalyzed asymmetric hydrogenation of α-acrylic acid, [18] [19] to build the 1,3-methyl unit of deoxypropionates. By varying the configuration of catalysts, the absolute and relative configuration of newly formed stereogenic centers can be controlled.…”
Section: Resultsmentioning
confidence: 99%
“…The diastereoisomeric ratio of product was determined after converting to amide with aniline. (4 (12 (13 (14 [(2R,3S,5S)-3-{[tert-Butyl(dimethyl)silyl]oxy}-5-(methoxymethoxy)-2,6-dimethylheptyl]-2,2-dimethyl-1,3-dioxane-4,6-dione (16 (17).…”
Section: General Procedures For Asymmetric Hydrogenations Of β-Keto Esmentioning
confidence: 99%
“…In 2011, Zhou et al demonstrated that the Ir/SpiroPAP catalyst may have a “metal-ligand bifunctional catalysis” mechanism similar to Noyori’s Ru/diphosphine/diamine system. Subsequently, iridium/SpiroPAP and iridium/SpiroPNS were applied to the asymmetric hydrogenation of β-keto esters by the same team, leading to excellent enantioselectivities (up to 99.9 and 95–99.9% ee, respectively) and an extremely high TON (1,230,000 and 355,000, respectively). Hu et al published an iridium catalyzed asymmetric hydrogenation of β - keto esters within chiral ferrocenyl P,N,N-ligands, providing good to excellent enantioselectivity.…”
Section: Introductionmentioning
confidence: 99%